The Advance in Partial Distribution: A New Mathematical Tool for Economic Management - Feng Dai; Ling Liang (Economics and Econometrics Research Institute (EERI), 2005)
In this paper, the Partial Distribution (PD) and multivariate Partial Distribution (MPD) are presented in their concepts, properties and applications, and PD is compared with the lognormal and the levy distribution. Though the levy distribution is better to describe the exchange returns in security market on a moderately large volatility range, the lognormal is better in a region of low values of volatility. We shall try to elucidate that Partial Distribution is better than lognormal distribution and levy distribution in many respects, and PD and MPD have some interesting properties which some other probability distributions have not. From PD and MPD, lots of interesting results can be acquired and many interesting economic propositions could be interpreted in analytic way. These properties could describe analytically many of phenomena in economic management better, and the results based on PD and MPD could be applied to solve many problems in economic management.
Keywords: C1; C2; C3; C4; C5; C8; 330; Partial Distribution; multivariate Partial Distribution; mathematical tool; economic management